2015
DOI: 10.1021/acs.langmuir.5b03271
|View full text |Cite
|
Sign up to set email alerts
|

Chain Length of Free Fatty Acids Influences the Phase Behavior of Stratum Corneum Model Membranes

Abstract: The skin, the largest organ of the human body, forms a flexible interface between our internal and external environment that protects our organism from exogenous compounds as well as excessive water loss. The stratum corneum (SC), the outermost layer of mammal epidermis, is mainly responsible for the skin impermeability. The SC is formed by corneocytes embedded in a lipid matrix, which is mostly constituted of ceramides (Cer), free fatty acids (FFA), and cholesterol (Chol), organized in two coexisting crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Upon heating above 60°C, the band position abruptly shifted toward high wavenumbers, reaching 2,095.6 cm 1 at 70°C. This value is characteristic of a disordered acyl chain (28,29) and the band shift was associated with the disordering of FFA24-d 47 chains, as previously observed for analogous mixtures (2,30). At low temperatures, the  s CH 2 band was found at around 2,850 cm 1 , a value indicative of high chain order (25,26).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Upon heating above 60°C, the band position abruptly shifted toward high wavenumbers, reaching 2,095.6 cm 1 at 70°C. This value is characteristic of a disordered acyl chain (28,29) and the band shift was associated with the disordering of FFA24-d 47 chains, as previously observed for analogous mixtures (2,30). At low temperatures, the  s CH 2 band was found at around 2,850 cm 1 , a value indicative of high chain order (25,26).…”
Section: Resultssupporting
confidence: 75%
“…The FFA24 spectrum at 37°C, with a width at the base of 128 kHz, indicated a transition of the fatty acid toward a gel phase. Upon heating up to 60°C, the evolution of the spectrum showed an increase of chain rotational diffusion while remaining in an almost all-trans configuration (2,24). Heating above 60°C caused a transition toward a liquid-ordered phase (l o ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FFAs found in the SC of healthy persons and AD patients showed variety in chain length distribution and saturation, which is in accordance with previous reports (Ananthapadmanabhan, Mukherjee, & Chandar, ; Mao‐Qiang, Elias, & Feingold, ; Paz Ramos & Lafleur, ). In the preliminary study, we applied the developed method to a smaller number of subjects to look for possible differences in FFA levels between AD patients and healthy controls.…”
Section: Resultssupporting
confidence: 92%
“…Ramos et al obtained a structurally uniform LM from N-lignoceroyld-erythro-sphingosine and lignoceric acid. [20] Pullmannvá found that LM, with CER containing a C24 hydrocarbon chain, showed a stronger barrier profile than CER possessing a C16 hydrocarbon chain. [21] An LM structural change was observed when the CER was replaced by the hydroxyl-group-added CER.…”
Section: Introductionmentioning
confidence: 99%